Characteristics of Australian and New Zealand osteopaths who treat patients presenting with non-musculoskeletal complaints: outcomes from two practice-based research networks - Brett Vaughan; Francesco Cerritelli; Jerry Draper-Rodi; Jack Feehan; Ana Paula A. Ferreira; Michael Fleischmann; Gopi McLeod; Cindy McIntyre; Chantal Morin; Lee Muddle; Oliver P. Thomson; Loïc Treffel; et al. (Chiropractic & Manual Therapies)
Abstract Background Australian and New Zealand osteopaths predominantly manage musculoskeletal complaints using a variety of modalities including manual therapy, exercise and lifestyle and occupational advice. There appears to be a small percentage of patients who seek osteopathy care for non-musculoskeletal issues such as conditions affecting the gastrointestinal tract. The evidence base for osteopathic treatment as part of the management of such conditions is equivocal. The aim of this study was to describe the practice of Australian and New Zealand osteopaths who report often treating patients with non-musculoskeletal complaints. Methods This study is a secondary analysis of data from the Australian and New Zealand osteopathy practice-based research networks (PBRNs) collected in Australia from July to December 2016 and in New Zealand from August to December 2018. Respondents to the PBRN baseline surveys were asked to provide information about their demographic, patient and clinical management characteristics. One of these characteristics was the frequency of treating patients presenting with non-musculoskeletal complaints. Descriptive and inferential statistics were used to inform regression modelling of significant predictors of often managing non-musculoskeletal complaints. Results Of the 1254 osteopath participants from Australia and NZ, 13.5% (n = 170) reported often treating patients presenting with non-MSK complaints. Significant predictors of often treating patients presenting with non-MSK complaints were often using visceral (ORa 3.54 95%CI 2.15–5.85) and Osteopathy in the Cranial Field (OCF) (ORa 2.05 95%CI 1.20–3.51) techniques, and often treating patients up to the age of 3 years (ORa 3.05 95%CI 1.89–4.90). Conclusion More than one in ten Australian and New Zealand osteopaths report often treating patients presenting with non-MSK complaints, with the dominant manual therapy approaches used being visceral techniques and OCF. This study provides a unique insight into the characteristics of osteopaths who often treat patients presenting with non-MSK complaints. Further research is required to examine if patients seek out care from an osteopath specifically for non-MSK complaints or primarily seek out care from an osteopath for MSK complaints but are managed for non-MSK complaints as a secondary consideration.